A comparative study of anti-leukemic effects of kaempferol and epigallocatechin-3-gallate (EGCG) on human leukemia HL-60 cells - Mohammad Hassan Jokar; Sima Sedighi; Maliheh Moradzadeh (Mashhad University of Medical Sciences, 2021)
Objective: Acute promyelocytic leukemia (APL) is among the most threatening hematological malignant cancers. Defects in cell growth and apoptotic pathways lead to the pathogenesis of the disease as well as its resistance to therapy; therefore, it is a good candidate for examining pro-apoptotic agents. The present study compared the molecular mechanism induced by kaempferol and epigallocatechin gallate (EGCG) as well as all-trans retinoic acid (ATRA) in HL-60 leukemia cells during five days. Materials and Methods: Cell viability was determined by resazurin assay following treatment with ATRA (10 µM), EGCG, and kaempferol (12.5-100 µM), and apoptosis was detected by the Anx V/PI kit. Moreover, the levels of genes involved in apoptosis (PI3K, AKT, BCL2, BAX, P21, PTEN, CASP3, CASP8, and CASP9) and multi-drug resistance (ABCB1 and ABCC1) were assessed by using real-time PCR test. Results: Based on the findings, kaempferol decreased cell viability and increased apoptosis in HL60 cells more than EGCG. Apoptosis was induced via extrinsic and intrinsic pathways in HL60 cells by kaempferol and EGCG. In addition, kaempferol and EGCG increased apoptosis and inhibited MDR in a concentration- and time-dependent manner. Conclusion: Kaempferol at high concentrations can be taken into consideration for treating patients with APL as compared with EGCG.